KEUNIKAN GARAP KENDANGAN MUDJIONO - Sri Joko Raharjo (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2013)
Basically this observation is done to get a picture about Mudjiono’s kendangan uniqueness phenomenon. Mudjiono as subject has musical’s talent pass through creative process so lays result as uniqueness garap kendangan. Mudjiono’s talent that as musical’s sensitivity, psycomotoric’s ability, and leadership soul that sharpened through esthetic experiences, contiguity with smiths karawitan, appreciation to happening karawitan phenomenon in society forms him as topnotch pengendang. A variety of Mudjiono’s view about the karawitan’s world and its creativity in developing garap kendangan was viewed as a controversial figure. This controversy is observable while compare by karawitan’s society argument in a general way.Key words: unique, garap, kendang